0% found this document useful (0 votes)
32 views

01 Correctness Proof of Iterative Algorithm

The correctness proof of the iterative algorithm is a way to solve the algorithm theorem. You can find the example of iterative algorithm problem-solving.

Uploaded by

poly tikoes
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
32 views

01 Correctness Proof of Iterative Algorithm

The correctness proof of the iterative algorithm is a way to solve the algorithm theorem. You can find the example of iterative algorithm problem-solving.

Uploaded by

poly tikoes
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 2

HOW TO PROVE THAT THESE ALGORITHMS ARE

CORRECT?

No. 1 function fib(n)


comment Return Fn
if n = 0 then return (0) else
a : = 0; b := 1; i :=2
while i < n do
c := a+b; a := b; b ;=c; i := i + 1
return(b)

No. 2 Proof for all n ∈ N, if 1 + x > 0, so (1 + x)n > 1 + nx

ANSWER No. 1

Recall on mathematical induction :

Claim for all n ∈ N,

𝑛(𝑛+1)
1+2+…+n= 2

When using induction to prove that some statement concerning the positive integer is true, the
following terminology is used :
1. The induction base is the proof that the statement is true fot n = 1 (or another initial
value)
2. The induction hypothesis is the assumption that the statement is true for an arbitrary n
> 1 (or another initial value)
3. The induction step is the proof that if the statement is true for n, it must be also true
for n + 1

Then

Induction base : for n = 1


1(1+1)
1= 2
(True)

Induction hypothesis : Assume, for an arbitrary positive integer n, that


𝑛(𝑛+1)
1+2+…+n= 2

Induction step : We need to prove that


(𝑛+1)(𝑛+2)
1 + 2 + … + n + (n + 1) = 2

To that end ,
𝑛(𝑛+1)
= 2
+ (n + 1)
𝑛2 +𝑛
= + (n + 1)
2
𝑛2 +3𝑛+2
= 2
(𝐧+𝟏)(𝒏+𝟐)
= 𝟐
(proved)

ANSWER No. 2

Claim for all n ∈ N,

Induction base : for n = 1


(1 + x)1 > 1 + 1.x (True)

Induction hypothesis : Assume, for an arbitrary positive integer n, that


(1 + x)n+1 > 1 + (n + 1)x

Induction step : We need to prove that


(1 + x)n+1 > 1 + (n + 1)x
(1 + x)n+1 > (1 + x)n (1 + x)1
(1 + x)n+1 > (1 + x) (1 + nx)
(1 + x)n+1 > 1 + (n + 1)x + nx2
nx2 must be > 0, then it can be excluded
(1 + x)n+1 > 1 + (n + 1)x (proved)

You might also like